CURAHAN WAKTU KERJA WANITA DALAM KEGIATAN USAHATANI PADI SAWAH DI DESA RASI SATU KECAMATAN RATAHAN KABUPATEN MINAHASA TENGGARA - Asti ., Unu; Martha M. Sendow; Welson M. Wangke (AGRI-SOSIOEKONOMI, 2018)
The aim of the study was to find out the time allocation of women's activities in wetland rice farming in the form of nursery activities, planting, weeding, fertilizing, harvesting until processing land, and controlling pests and diseases only carried out by men. The outpouring of a woman's work time in productive activities depends a lot on socio-economic factors and the condition of her family. Socio-economic factors that influence the outpouring of working time for female farmers are age level, number of family dependents, wage level, land area, marital status, education level, and level of experience. The study lasted for 4 (four) months starting from April to July 2018 in Rasi Satu Village, Ratahan District, Southeast Minahasa Regency. The data used are primary data collected through interviews with 20 women farmers as respondents. Secondary data was obtained from the Rasi Satu Village office. The analysis used is descriptive in table form. The results showed that the outpouring of working time of women in wetland farming in Rasi Satu Village was at nursery activities of 6.86%, planting of 22.08%, weeding of 20.26%, fertilization of 10.06%, harvest of 40.74%. But land management, and control of pests and diseases is only done by men.*eprm*.